Regional differences in adipose tissue development: effects of nutritional challenges on genes involved in insulin, insulin like growth factor and glucocorticoid signalling - Bos, Petra Marianne (2010)
Adipose tissue development is regulated by a complex interaction between the local actions of insulin, glucocorticoids and insulin like growth factors (IGFs). A series of experiments was undertaken in which the normal development of individual adipose tissue depots and their development following periconceptional under- and overnutrition, formula feeding and juvenile obesity was investigated in sheep. Expression and abundance of glucocorticoid receptor (GR), 11β-hydroxysteroid dehydrogenases (11β-HSDs), insulin receptor, p85 subunit of phosphatidylinositol 3-kinase (p85), glucose transporter 4 (Glut4), insulin like growth factor (IGF) 1 and 2 and their receptors (IGF-R) were measured as markers of sensitivity to glucocorticoids, insulin and IGFs in individual adipose tissue depots.